A state-of-the-art review: toward a novel vehicle dynamics control concept taking the driveline of electric vehicles into account as promising control actuators. Issue 7 (3rd July 2021) - Katsuyama, Etsuo; Yamakado, Makoto; Abe, Masato
Abstract : The era of the electrification of vehicle drivelines is rapidly approaching. Motors are capable of providing controls with response and accuracy two orders of magnitude greater than internal combustion engines. It is also relatively simple to design a driveline capable of independently controlling the driving force at each wheel by providing compact motors throughout the vehicle. Although the potential of such driving force distribution control in improving vehicle dynamic performance has been a serious topic of research since even before the current wave of driveline electrification, the complex mechanisms required to realise these controls have prevented mass adoption. However, it seems that these research efforts are finally reaching a stage where practical adoption might be possible. This state-of-the-art review examines the background and most recent research related to vehicle dynamics control, particularly controls that use electrical drive units, and investigates the topics of interest and trends of a wide range of researchers. Subsequently, taking into account ongoing efforts to pair vehicle dynamics controls with electrical actuators, this review also discusses a novel control architecture that depart from control design methods formulated in the past by researchers across the field, and points the way toward the future of vehicle dynamics control research.